2007
DOI: 10.1111/j.1365-2109.2007.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air exposure on the lysosomal membrane stability of haemocytes in blacklip abalone, Haliotis rubra (Leach)

Abstract: The neutral red retention (NRR) assay was used to evaluate the effects of air exposure on lysosomal membrane integrity in the haemolymph of blacklip abalone, Haliotis rubra, and its subsequent recovery in water. After acclimation in 16°C water for 7 days, abalone were exposed to an air temperature of 7, 16 or 23°C for 12 h in the air exposure experiment or to these three air temperatures, e.g., for 12, 24 or 36 h, followed by re‐immersion in 16°C water in the lysosomal membrane stability recovery experiment. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Recently, neutral red retention (NRR) assay has also been used to assess the immune status of shellfish by measuring the dye retention time of lysosomal membranes [45]. Neutral red is a cytotoxic weak base [46] and has been successfully used in the neutral red retention (NRR) assay as a biomarker to test the stability of lysosomal membranes in aquatic animals [35,[47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, neutral red retention (NRR) assay has also been used to assess the immune status of shellfish by measuring the dye retention time of lysosomal membranes [45]. Neutral red is a cytotoxic weak base [46] and has been successfully used in the neutral red retention (NRR) assay as a biomarker to test the stability of lysosomal membranes in aquatic animals [35,[47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Neutral red is a cytotoxic weak base [46] and has been successfully used in the neutral red retention (NRR) assay as a sensitive indicator of lipid membrane integrity in cases of bacterial infection and immunostimulant toxicity in shellfish. [35,[47][48][49][50][51]. Lysosomes found within the semi-granular and granular haemocytes are polymorphic, hydrolytic enzyme-containing organelles that have the capacity to take up and retain neutral red dye.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al () also reported that dietary supplementation of 30 g/kg fermented CBP with Bacillus subtilis lowered cumulative mortality of olive flounder when fish were fed for 6 weeks and then infected with Edwardsiella tarda . Air exposure stressor affected the physiological state as well as performance (survival and growth) of abalone (Hooper et al, ; Morash & Alter, ; Song et al, ). Several studies reported that citrus peel has not only antioxidant activity (Ghasemi, Ghasemi, & Ebrahimzadeh, ; Rehman, ; Tripoli, Guardia, Giammanco, Majo, & Giammanco, ), but also high amount of vitamin C (ascorbic acid), which improves immunity of aquatic animals (Ai et al, ; Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lysosomal membrane stability declines with increasing air temperature during transport and takes longer to recover upon re‐immersion (Song et al . ).…”
Section: Physiological Response To Farmingmentioning
confidence: 97%